Does copper undergo surface roughening during fatigue in the VH regime? - Stanzl-Tschegg, Stefanie; Mughrabi, Hael; Schuller, Reinhard (Fracture of Nano and Engineering Materials and Structures - Proceedings of the 16th European Conference of Fracture, 2006)
Extensive studies have been performed on nature and formation of persistent slip bands (PSBs) in the past. They have been identified as sites of localized cyclic plastic deformation, which are typically found in fcc metals, like copper, nickel or solid solutions of these metals. These sites of plastic deformation become visible as extrusions and microcracks (intrusions) on the specimen surface and as “ladder”, “vein” or cell structures of the dislocations in the interior of the specimen. The stresses and plastic strains for their formation are determined by a plateau stress in the cyclic stress strain curve (CSS curves) [1] with a typical plateau stress at approximately 28 MPa and a resolved shear strain between approximately 10−4 and 8×10−3 for copper single crystals. Additional investigations have been performed at stresses below the plateau regime at stresses between 3 and 26 MPa and number of cycles up to several 107 in order to study the evolution of sliding and dislocation characteristics [2].<br
Created from Fastlane, Scopus look-up